2010
DOI: 10.4103/0974-7788.59939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diashis, a polyherbal formulation, in streptozotocin-induced diabetic male albino rats

Abstract: This study focuses on the effect of ‘Diashis’, a polyherbal formulation composed of eight medicinal plants for the management of streptozotocin (STZ)-induced diabetes in rats. As oxidative stress is one of the consequences of diabetes, the activities of hepatic antioxidant enzymes and metabolic enzymes were evaluated. Treatment with ‘Diashis’ in STZ-induced diabetic rats resulted in a significant (P < 0.01) recovery in the activities of hepatic hexokinase, glucose-6-phosphate dehydrogenase, and glucose-6-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Many polyherbal formulation such as Okudiabet [5] Diashis [6], Diasulin [7] etc. have revealed their efficacy and potency against diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Many polyherbal formulation such as Okudiabet [5] Diashis [6], Diasulin [7] etc. have revealed their efficacy and potency against diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, diabetic rats showed a significant increase of glucose associated to a significant decrease of insulin, level, compared to their respective values in the control group. This could be explained by the fact that STZ induces degeneration in Langerhans islet beta cells [33][34][35]. The administration of sucralose to diabetic rats has no effect on insulin while reduces glucose level, compared to diabetic rats receiving distilled water.…”
Section: Discussionmentioning
confidence: 99%
“…Such effect may be explained in part by either a decrease in the rate of intestinal glucose absorption [23-25] or an increase in peripheral glucose utilization [24,25]. In this line, some authors have ascertained increased catabolism of glucose due to GLUT4 translocation to the plasma membrane in muscle and brown adipose cells [19,20], with up-regulation of the uncoupling protein-1 in brown adipose tissue and hepatic gluconeogenesis [25,26], causing as a result hyperinsulinemia or enhancement of peripheral glucose utilization [19,27,28]. Moreover, a possible stimulatory mechanism on the few surviving β-cells has been considered, which could allow the release of more insulin [29-32].…”
Section: Discussionmentioning
confidence: 99%